A pilot and feasibility study of the plasma and tissue pharmacokinetics of cefazolin in an immature porcine model of pediatric cardiac surgery. Issue 11 (15th September 2015) - Kilbaugh, Todd J.; Himebauch, Adam S.; Zaoutis, Theoklis; Jobes, David; Greeley, William J.; Nicolson, Susan C.; Zuppa, Athena F.; Anderson, Brian
Summary Background Surgical site infection (SSI) prevention for children with congenital heart disease is imperative and methods to assess and evaluate the tissue concentrations of prophylactic antibiotics are important to help maximize these efforts. Aim The purposes of this study were to determine the plasma and tissue concentrations with standard of care, perioperative cefazolin dosing in an immature porcine model of pediatric cardiac surgery, and to determine the feasibility of this model. Methods Piglets (3–5 days old) underwent either median sternotomy (MS) or cardiopulmonary bypass with deep hypothermic circulatory arrest (CPB + DHCA) and received standard of care prophylactic cefazolin for the procedures. Serial plasma and microdialysis sampling of the skeletal muscle and subcutaneous tissue adjacent to the surgical site was performed. Cefazolin concentrations were measured, noncompartmental pharmacokinetic analyses were performed, and tissue penetration of cefazolin was assessed. Results Following the first intravenous dose, maximal cefazolin concentrations in the subcutaneous tissue and skeletal muscle were similar between groups with peak tissue concentrations 15–30 min after administration. After the second cefazolin dose given with the initiation of CPB, total plasma cefazolin concentrations remained relatively constant until the end of DHCA and then decreased while muscle‐ and subcutaneous‐unbound cefazolin concentrations showed a second peak during or after rewarming. For the MS group, 60–67% of the intraoperative time showed subcutaneous and skeletal muscle concentrations of cefazolin >16 μg·ml−1 while this percentage was 78–79% for the CPB + DHCA group. There was less tissue penetration of cefazolin in the group that underwent CBP + DHCA (P = 0.03). Conclusions The cefazolin dosing used in this study achieves plasma and tissue concentrations that should be effective against methicillin‐sensitive Staphylococcus aureus but may not be effective against some gram‐negative pathogens. The timing of the cefazolin administration prior to incision and a second dose given during cardiopulmonary bypass may be important factors for achieving goal tissue concentrations.